Association between an educational intervention and a reduction in inappropriate troponin testing in patients presenting to an adult emergency department. Issue 11 (November 2014) - Scorgie, R.; Nicholls, G. M.; Jones, P.
Abstract: Background: High‐sensitivity troponin replaced the fourth generation assay at our institution in July 2010. Prior experience suggested that the number of positive tests with the new assay may double, and that many troponin requests were inappropriate. Aim: Primarily, this study aims to design and measure the effect of an educational intervention to reduce the number of inappropriate troponin tests. Second, other objectives are to compare weekly totals of troponin tests before and after the intervention, to note patients with missed acute coronary syndrome (ACS) during the study period and to survey clinicians regarding their likely troponin ordering practices in certain clinical scenarios. Methods: A staff survey informed the content of the educational intervention. Criteria for inappropriate testing were defined prior to the study. Retrospective notes review of pre‐and post‐intervention cohorts were used to determine the reduction in inappropriate troponin tests. Results: Ninety‐six patients were in each cohort. The proportion of inappropriate tests fell from 43% (95% confidence interval (CI) 33–53) pre‐intervention to 22% (95% CI 14–31) post‐intervention, P = 0.002. Weekly total of troponin tests performed decreased from a mean of 298 (95% CI, 290–307) pre‐intervention to 244 (95% CI 232–255) post‐intervention, P < 0.001. No cases of missed ACS were found; all cause mortality was unchanged following the intervention. Conclusion: Our educational intervention was associated with a reduction in inappropriate use of troponin tests and a reduction in the total number of tests requested, with no known missed ACS. Others faced with a change to a high‐sensitivity assay should consider a similar intervention.